THE SYNTACTIC ANALYSIS OF DECLARATIVE SENTENCES IN BBC NEWS ARTICLES AND ITS APPLICATION IN TEACHING GRAMMAR FOR THE TWELFTH GRADE OF VOCATIONAL HIGH SCHOOL - Sari Saraswati; Andrian Nuriza Johan (p-ISSN 2356-0576, 2020)
Abstract. This research is concerned with the sentence structure of declarative sentences found in BBC New’s articles. The aims of this research are to identify the syntactic structure of declarative sentences in the articles of technology of BBC News and to describe the application of declarative sentences in the articles of technology in teaching grammar for the twelfth grade of vocational high school. This research belongs to descriptive qualitative research because the data of this research is collected by classifying the declarative sentences found in the technology articles and the researcher as the key instrument. In collecting the data, the researcher chose, read, selected the technology articles, and arranged the data of declarative sentences from those articles. In analysing the data, the researcher identified, classified, counted , discussed the finding, applied the research finding in teaching grammar, and drew conclusion and suggestion. The result of this research shows that there are 103 declarative sentences found in technology articles of BBC News published in January 2020. Based on the types of declarative sentences, there are four types found. There are 57 simple sentences (55.34%), 5 compound sentences (4.85%), 36 complex sentences (34.96%), and 5 compound-complex sentences (4.85%). This research can be applied in teaching grammar for the twelfth grade of vocational high school. Keywords: Syntactical Analysis, Declarative Sentences, BBC News, teaching grammar.